Terrestrial vertebrate diversity of caves and limestone forests in southern Sierra Madre Mountain Range, Luzon Island, Philippines - Duco, Renz Angelo J.; De Guia, Anna Pauline O.; Dimalibot, Judeline C; Parcon, Julius A.; Cosico, Edison A.; Malizon, Charlie R; Aguila, Ammie R; Alviola, Philip A.; Gonzalez, Juan Carlos (2023)
The caves and karst forests of southern Sierra Madre are a unique and understudied habitat that is home to a high number of endemic and globally threatened species. These habitats provide essential resources for the local terrestrial vertebrate fauna, although increasing anthropogenic disturbances pose a serious threat to existing wildlife populations. Here, we provide an inventory of terrestrial vertebrate fauna of caves and limestone forests of three ecotourism areas within the southern Sierra Madre in CALABARZON Region, Philippines. A combination of various field survey methods (i.e. line transect surveys, mist netting, opportunistic catching, cage trapping) was conducted from 2021–2023 to determine the diversity of amphibians, reptiles, non-volant mammals, bats, and birds in the three sites. A total of 160 species (13 amphibians, 23 reptiles, 98 birds, four non-volant mammals, and 22 bats) were recorded in this study. Endemicity was high at 46% with 56 Philippine endemics, including 21 species endemic to the Greater Luzon Island. In addition, we recorded 18 locally and globally threatened species based on the IUCN Red List and DENR-DAO 2019-09. The high species richness and presence of threatened species underline the high conservation value of the study areas. However, unmanaged growth of tourism and habitat fragmentation threaten their biodiversity. The data generated will be used to guide the classification, proper management, and conservation of these karst areas, caves, and their resources by the national government and local government units.
Keywords: Endemic animals; Sierra Madre (Luzon); Terrestrial ecosystems